The impact of Staphylococcus saprophyticus on the fermentation of cigar filler tobacco leaves and the dynamics of microbial community - Yao, Lan; Zhao, Zhongde; Li, Linwei; Yu, Jun; Yang, Jinpeng; Yang, Chunlei; Chen, Xiong (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionStaphylococcus has garnered increasing attention for its role in improving fermentation results and promoting the biosynthesis of aromatic compounds.MethodsThis study investigated the effects of exogenously introduced Staphylococcus saprophyticus on the microbial community structure, functional gene expression, and volatile aroma profiles during the fermentation of cigar filler leaves.ResultsThe results demonstrated that S. saprophyticus significantly enhanced the accumulation of alcohols and ketones. LEfSe analysis identified Bacillus as a key differential genus in the inoculated group. Spearman correlation analysis revealed positive associations between Staphylococcus and Bacillus, as well as with key aroma compounds such as 1-methyl-4-(2-methyloxiranyl)-7-oxabicyclo [4.1.0] heptane and cis-6-nonenal. EGGNOG functional annotation indicated upregulation of carbohydrate and amino acid metabolism pathways. Additionally, CAZy analysis revealed increased abundance of glycosyltransferases and carbohydrate-binding modules, which may facilitate sugar conversion and utilization.DiscussionThese findings provide a theoretical basis for the application of exogenous microorganisms in cigar fermentation and offer insights into the regulation of microbial community structure for quality improvement.